Social protest and the political economy of sectarianism in Lebanon. Issue 4 (1st October 2016) - Baumann, Hannes
ABSTRACT: Lebanon sees frequent socio-economic protests, which defy the sectarian logic of politics prevalent in the country. Why does sectarianism assert itself as the dominant political cleavage regardless of these socio-economic struggles? I examine the repression of trade union protests for greater social justice in the 1990s. The politicisation of sectarianism requires the depoliticisation of alternative social visions, for instance along socio-economic lines. While most accounts of the politicisation of sectarianism focus on citizens' consent to a sectarian vision of politics sold to them by "ethnopolitical entrepreneurs", I argue that there is also an element of coercion involved. The political economy of Lebanese sectarianism is one where a small politically connected elite appropriates the bulk of economic surplus and redistributes it through communal clientelism. Social protest challenges the sectarian elite cartel: A more just distribution of wealth and incomes would reduce demand for patronage resources "from below" and politicians would lose control of resources "from above" to redistribute along communal lines. The paper consists of three parts. The first part situates Lebanon in the literature on ethnicity and nationalism. This article contributes to a new direction in studies of ethnicity and nationalism which goes beyond the macro-historical bias of much of this literature. The second section explains how the neo-liberal reconstruction driven by businessman-prime minister Rafiq Hariri in the post-civil war period resulted in the concentration of wealth and incomes at the top and the reliance of the majority of the population on resources controlled by politicians. Post-war reconstruction reproduced sectarian clientelism in Lebanon. The third section shows how trade unions became the main challenger of this economic policy in the 1990s. Lebanon's politicians reacted with repressive measures: They banned street demonstrations, called in the army, split the confederation of trade unions in its 1997 election, and created pseudo-unions tied to their own interests.